Public health nursing : population-centered health care in the community - Lancaster, Jeanette; Stanhope, Marcia (Elsevier Mosby, 2012)
Gives you a foundation in community and public health nursing concepts and interventions for individuals, families, and communities. This title includes health promotion and disease prevention concepts that are integrated into the multifaceted role of population-focused, community-oriented nursing practice